Neutrophil elastase inhibitor (Sivelestat) in the treatment of acute respiratory distress syndrome induced by COVID-19: a multicenter retrospective cohort study - Yuting Li; Jianjun Zhao; Jiahui Wei; Yanhong Zhang; Haitao Zhang; Ying Li; Ting Liao; Yang Hu; Bo Yuan; Xinmei Zhang; Wanyan Liu; Changgang Liu; et al. (Respiratory Research)
Abstract Background Recent studies suggest that neutrophil elastase inhibitor (Sivelestat) may improve pulmonary function and reduce mortality in patients with acute respiratory distress syndrome. We examined the association between receipt of sivelestat and improvement in oxygenation among patients with acute respiratory distress syndrome (ARDS) induced by COVID-19. Methods A large multicentre cohort study of patients with ARDS induced by COVID-19 who had been admitted to intensive care units (ICUs). We used propensity score matching to compare the outcomes of patients treated with sivelestat to those who were not. The differences in continuous outcomes were assessed with the Wilcoxon signed-rank test. Kaplan–Meier method was used to show the 28-day survival curves in the matched cohorts. A log-rank P-test stratified on the matched pairs was used to test the equality of the estimated survival curves. A Cox proportional hazards model that incorporated a robust sandwich-type variance estimator to account for the matched nature of the data was used to estimate hazard ratios (HR). All statistical analyses were performed with SPSS 26.0 and R 4.2.3. A two-sided p-value of < 0.05 was considered statistically significant. Results A total of 387 patients met inclusion criteria, including 259 patients (66.9%) who were treated with sivelestat. In 158 patients matched on the propensity for treatment, receipt of sivelestat was associated with improved oxygenation, decreased Murray lung injury score, increased non-mechanical ventilation time within 28 days, increased alive and ICU-free days within 28 days (HR, 1.85; 95% CI 1.29 to 2.64; log-rank p < 0.001), shortened ICU stay and ultimately improved survival (HR, 2.78; 95% CI 1.32 to 5.88; log-rank p = 0.0074). Conclusions Among patients with ARDS induce by COVID-19, sivelestat administration is associated with improved clinical outcomes.